2019
DOI: 10.3389/fonc.2019.01377
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant RON and MET Co-overexpression as Novel Prognostic Biomarkers of Shortened Patient Survival and Therapeutic Targets of Tyrosine Kinase Inhibitors in Pancreatic Cancer

Abstract: RON (recepteur d'origine nantais) and MET (hepatocyte growth factor receptor) are tyrosine kinase receptors. Various cancers have aberrant RON and MET expression and activation, which contribute to cancer cell proliferation, invasiveness, and metastasis. Here, we explored RON and MET expression in pancreatic cancer and their relationship with overall survival (OS) time, and evaluated their significance as therapeutic targets of tyrosine kinase inhibitors in pancreatic cancer. We enrolled 227 patients with panc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 46 publications
2
9
0
Order By: Relevance
“…Notably, violin plots of gene expression by pathological stages based on the TCGA PAAD data showed that twenty-one of the identified prognostic genes (ITGB6, LAMC2, KRT7, SERPINB5, IGF2BP3, IL1RN, MPZL2, SFTA2, MET, LAMA3, ARNTL2, SLC2A1, LAMB3, COL17A1, EPSTI1, IL1RAP, AK4, ANXA2, S100A16, KRT19, and GPRC5A) also significantly correlated with pathological stages of the disease, indicating that these genes may play crucial roles in the tumorigenesis of PDAC. As expected, some of these identified genes have been reported to be associated with poor overall survival of patients with pancreatic cancer ( Cheng et al, 2019 ; Hu et al, 2019 ; Jahny et al, 2017 ; Pei, Yin & Liu, 2018 ; Reader et al, 2019 ; Schaeffer et al, 2010 ; Takahashi et al, 2019 ; Wu et al, 2019 ; Yao et al, 2016 ; Zhang et al, 2019 ). However, the functional and clinicopathological significance of IL1RN, MPZL2, SFTA2, EPSTI1, IL1RAP, AK4 and S100A16 in PDAC have not been reported.…”
Section: Discussionsupporting
confidence: 73%
“…Notably, violin plots of gene expression by pathological stages based on the TCGA PAAD data showed that twenty-one of the identified prognostic genes (ITGB6, LAMC2, KRT7, SERPINB5, IGF2BP3, IL1RN, MPZL2, SFTA2, MET, LAMA3, ARNTL2, SLC2A1, LAMB3, COL17A1, EPSTI1, IL1RAP, AK4, ANXA2, S100A16, KRT19, and GPRC5A) also significantly correlated with pathological stages of the disease, indicating that these genes may play crucial roles in the tumorigenesis of PDAC. As expected, some of these identified genes have been reported to be associated with poor overall survival of patients with pancreatic cancer ( Cheng et al, 2019 ; Hu et al, 2019 ; Jahny et al, 2017 ; Pei, Yin & Liu, 2018 ; Reader et al, 2019 ; Schaeffer et al, 2010 ; Takahashi et al, 2019 ; Wu et al, 2019 ; Yao et al, 2016 ; Zhang et al, 2019 ). However, the functional and clinicopathological significance of IL1RN, MPZL2, SFTA2, EPSTI1, IL1RAP, AK4 and S100A16 in PDAC have not been reported.…”
Section: Discussionsupporting
confidence: 73%
“…Activation of several intracellular signaling pathways that is mediated by MET has led to the emergence of diverse cellular hallmarks of cancer, including cell proliferation, survival, invasion, migration, metastasis and inhibition of apoptosis (50)(51)(52). MET may be involved in the malignant process of pancreatic cancer, and can serve as a biomarker for assessing the prognosis of patients with pancreatic cancer (53). IL1R2, as an endogenous inhibitor, can be highly expressed in the follicular helper T cells of mice, and the specific marker molecules, such as IL1R2, on the surface of tumor infiltrating Treg cells in colorectal cancer and non-small cell lung cancer have also been demonstrated to be upregulated (54,55).…”
Section: Discussionmentioning
confidence: 99%
“…Among human pancreatic tissue samples, RON expression was detected in 83% of metastatic lesions, 79% of primary lesions, and 93% of high-grade PanIN using immunohistochemistry, with low expression being detected in low-grade PanIN and normal ducts (18% and 6%, respectively), suggesting that RON might function in pancreatic carcinogenesis and metastatic progression[ 22 ]. Moreover, RON expression levels were significantly related to overall survival in patients with pancreatic cancer, indicating that RON could be an important indicator of prognosis in pancreatic cancer[ 75 ]. Conflicting results between RON expression and pancreatic cancer prognosis were found in an early study[ 76 ], thus more research is needed to determine the utility of RON as a prognostic biomarker in patients with pancreatic cancer.…”
Section: Ron Receptor and Pancreatic Cancermentioning
confidence: 99%